Impact of newly constructed primary healthcare centres on antenatal care attendance, facility delivery and all-cause mortality: quasi-experimental evidence from Taabo health and demographic surveillance system, Côte d'Ivoire. Issue 1 (31st January 2022) - Koné, Siaka; Bonfoh, Bassirou; Probst-Hensch, Nicole; Utzinger, Jürg; N'Goran, Eliézer K; Fink, Günther
Abstract : Objectives: Access to quality care remains limited, particularly in low-income and middle-income countries. Although better health outcomes for families living in close proximity to healthcare facilities have been documented in cross-sectional studies, evidence on the extent to which additional health facilities can contribute to improved population health remains scanty. We aimed to estimate the causal impact of newly constructed primary healthcare facilities within a health and demographic surveillance (HDSS) site in Côte d'Ivoire. Design: We conducted a quasi-experimental study. Logistic and Cox proportional hazards regression models were used to estimate the impact of new healthcare facilities on healthcare-seeking behaviour and all-cause mortality. Setting: Data were collected prospectively through the Taabo HDSS located in south-central Côte d'Ivoire between 2010 and 2018. Participants: We analysed 2957 deaths across 440 973 person-year observations as well as 14 132 live births. Primary outcome measures: The primary outcomes were antenatal care (ANC) attendance, facility delivery and mortality. Logistic and Cox proportional hazards models were employed to estimate the impact of the new health facilities on ANC attendance, facility delivery and child as well as adult mortality. Results: Average distance to the nearest healthcare facility declined from 5.5 km before to 2.8 km after opening of four new healthcare facilities in targeted villages. No improvement was observed for ANC attendance, institutional deliveries and adult mortality. New facilities reduced the risk of post-neonatal infant mortality by 46% (HR 0.54, 95% CI 0.31 to 0.94, p<0.05), suggesting a mortality gradient of 2 deaths per 1000 for each additional km (Coef=0.002, 95% CI 0.000 to 0.004, p<0.05). Conclusions: Our results suggest that new facilities do not necessarily improve healthcare utilisation and health outcomes. Further research is needed to identify the best ways to ensure access to quality care in resource-constrained settings.